Letter from Max Bredig to Georg Bredig and Marianne Homburger, January 1936 - Bredig, Max Albert (1936)
Max Albert Bredig (1902-1977) writes a letter to his father, Georg Bredig (1868-1944), and sister, Marianne Homburger (1903-1986). Max tells his family that he has been taking Hebrew lessons twice a week, but thinks it would be more practical for him to learn English instead.
Keywords: Homburger, Marianne, 1903-1986; Bredig, Georg, 1868-1944; Bredig, Max Albert, 1902-1977; Nord, Friedrich Franz, 1889 -1973; Chemistry; Hebrew language